PENGEMBANGAN MEDIA RODA PUTAR KANTONG AJAIB UNTUK MENGENAL KONSEP BILANGAN BERMAKNA ANAK USIA 4-5 TAHUN - Ari Kesuma, Virdawati; Rosalina Arifin, Citra Dewi (GCEJ (Golden Childhood Education Journal), 2024)
ABSTRACT This development research is motivated by the lack of children's interest in knowing the concept of numbers due to the use of monotonous learning media which makes children uninterested and feels depressed, so that innovation is needed in developing learning media that can make it easier for children to recognize the concept of numbers. Learning media as a learning companion must have good feasibility values ​​so that the problem formulation is how to develop media based on content or material aspects and media aspects to recognize the concept of meaningful numbers for children aged 4-5 years. The development of learning media for the Magic Bag Spin Wheel is designed based on the principles of learning media that are suitable for early childhood. This development research aims to develop a magic bag rotating wheel media in recognizing the concept of meaningful numbers for children aged 4-5 years. This research uses the research development method (Research & Development) which uses 5 of the 10 steps proposed by Sugiyono according to the needs, namely 1) Potential and problems, 2) Data collection, 3) Product Design, 4) Design validation, 5) Design Revision. The data collection instrument used a questionnaire in the form of a material expert validation sheet and a media expert validation sheet. The data analysis technique used on product quality is descriptive data analysis. Furthermore, the data obtained were analyzed using a Likert scale. From the results of data analysis, it can be obtained the results of the validation of the media expert's feasibility with an average of 3.5 with a percentage of 87.5% and an average score of validation of material experts with an average of 3.25 with a percentage of 81.3%. Thus the average scoring by the experts is 3.38 with a percentage of 84.4% which is included in the very feasible criteria, so that the magic bag rotating wheel media to recognize the concept of meaningful numbers for children aged 4-5 years being developed is very feasible to use.